Terrestrial environmental DNA survey substantially improves detection of satellite populations for an invasive insect - Julie L. Lockwood; Michael C. Allen; Anthony R. Vastano; Mario F. Hernandez; Christopher Eddy; Mariel Vandegrift; Kathleen E. Kyle; Caleb Truscott (Biological Invasions, 2026)
Early detection of satellite populations is essential for managing invasive species, but traditional methods often fall short when populations are sparse and widespread. We assessed the effectiveness of terrestrial environmental DNA (eDNA) surveys for detecting spotted lanternfly ( Lycorma delicatula ) along major highways in New York State, USA, a region at the invasion front in North America. Over 2 years, we sampled 83 sites covering 1,650 km of high-traffic roadway using a roller-based, host-tree surface eDNA collection method and compared results with concurrent visual surveys and a government-run trap surveillance program (‘circle traps’). We detected spotted lanternfly eDNA at 77% of sampled sites, while visual surveys indicated lanternfly presence at only 5% of these sites. On average, the delay between positive spotted lanternfly detection with eDNA and an eventual iNaturalist record was 662 days. Site occupancy models estimated detection probability at 0.77 per eDNA sample (95% CI 0.66–0.86), compared with 0.25 per trap (95% CI 0.21–0.31). Detection probability was lower in 2023 than in 2022 (eDNA: 0.68 vs. 0.89; traps: 0.13 vs. 0.32), likely due to our sampling in locations with lower population densities and distances farther from the invasion core. Extrapolation from hierarchical models indicated that three eDNA samples per occupied site would achieve a 95% cumulative detection probability, whereas circle traps would require 11–23 checks. Our surveys identified previously undocumented spotted lanternfly populations beyond the known range front at the time of the survey, including in high-risk agricultural and forested areas. These results show that terrestrial eDNA surveys can outperform traditional methods in detecting low-abundance invasive insects across large areas. Incorporating eDNA into early detection and rapid response efforts for terrestrial invasive species may improve management outcomes and reduce the risk of uncontrolled spread caused by human dispersal.

Changes to Skin Microbiome Community Dynamics Support Resistance to Enzootic and Epizootic Strains of Batrachochytrium dendrobatidis (Bd) in the Spotted Salamander ( Ambystoma maculatum ) - Tucker W. Cambridge; Christopher J. Kyle; David Lesbarrères; Dennis L. Murray (Molecular Ecology, 2026)
Global spread of animal pathogens has contributed to species declines and extinctions. In regions where a particular disease is enzootic, pathogen inhibition may arise through protection provided by host‐associated microbiomes. Amphibians skin microbiomes can inhibit growth of the fungal pathogen Batrachochytrium dendrobatidis (Bd), preventing emergence of disease through a range of microbe‐mediated antifungal mechanisms, allowing hosts to resist Bd infection. However, it remains unclear how skin microbiomes may shift in community composition or structure following infection by different Bd strain types. We assessed infection dynamics of Bd‐resistant amphibians ( Ambystoma maculatum ) following experimental exposure to enzootic and epizootic strains of Bd‐GPL and tracking pathogen load and bacterial skin microbiome community responses from exposure through to recovery, using 16S rRNA metabarcoding. We found that microbiome communities shifted post‐exposure, with increasing diversity, dominance, abundance and total proportion of known Bd‐inhibitory microbes, indicating microbial rescue effects during infection. We also observed lower intra‐host variation in diversity during recovery, indicating a shared functional response across the host population and broadly indicative of microbial community resilience. Salamanders exposed to enzootic Bd had greater pathogen loads over time and demonstrated more prolonged community changes and more putatively protective microbiomes, whereas epizootic Bd infection was more rapidly cleared following temporary increase in inhibitory microbes. Collectively, these results indicate that skin microbiomes may offer a crucial barrier to fungal disease in Bd‐resistant amphibians, with exposure to pathogens inducing changes in microbial community structure that benefit hosts, possibly driven by localized coevolutionary changes in infection dynamics. Our work illustrates how complex host‐pathogen interactions are mediated by skin microbiomes through changes in microbial community dynamics that favour pathogen resistant microbes.

Twelve distinct laboratory methods used to measure SARS-CoV-2 in wastewaters throughout a three-year Ontario-wide, Canada study: Impact on public health interpretation of disease incidence - Nada Hegazy; K. Ken Peng; Johanna de Haan-Ward; Elizabeth Renouf; Elizabeth Mercier; Shen Wan; X. Joan Hu; Charmaine Dean; Mark Servos; Elizabeth Edwards; Gustavo Ybazeta; Marc Habash; et al. (Journal of Water Process Engineering, 2026)

Dietary nitrate supplementation does not improve resistance exercise performance in resistance-trained women - Sydney N. Brennan; Justin M. Foster; Raymond T. Gerardo; Trevor J. Molnar; Ryan Tran; Christopher B. Sottile; Kyle S. Geppert; Michael Egiazarian; Abigail F. Ballhagen; Money Ghimire; John R. M. Renwick; Lewis A. Gough; et al. (European Journal of Applied Physiology, 2026)

Adaptive Modeling to Inform Environmental Management - Katie Irving; Rupert Mathwin; Christopher J. Kotalik; J. Angus Webb; David M. Walters; Siwan Lovett; S. Kyle McKay; Christa L. Torrens; John R. Olson; Ziad A. El Jack (Environmental Management, 2026)

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Shortleaf Pine (Pinus echinata): Management Challenges, Knowledge Gaps, and Opportunities for an Unsung Species - Benjamin O. Knapp; Jacob Fraser; Joanne Baggs; Vikram E. Chhatre; David Clabo; Connor D. Crouch; Daniel C. Dey; Shaik M. Hossain; Steven B. Jack; John M. Kabrick; Kathryn R. Kidd; Steven McNulty; et al. (Journal of Forestry, 2026)
Shortleaf pine has the broadest range of the southern pine species, occurring in 22 states and extending north into New Jersey, Pennsylvania, and New York (Staten Island). Shortleaf pine has been understudied compared to loblolly pine and longleaf pine, typically favored for timber production and conservation value, respectively. The extensive range of shortleaf pine contributes to a high degree of variability within and among its ecosystems and contributes to the need to understand regional context in considering its ecology and management. The goal of this paper is to review and synthesize the state-of-knowledge on shortleaf pine ecosystems, emphasizing the importance of variation across its range in identifying management challenges and opportunities. We discuss the variation in growing conditions that occur across the geographic range, shortleaf pine natural community groups, and contemporary shortleaf pine forest types that occur on the landscape. We provide a review of the state-of-knowledge for topics related to shortleaf pine management, including its fire ecology, genetic considerations, economics, and others. Finally, we synthesize these into key considerations and highlight regionally specific management challenges and opportunities.

Residual effects of a localised diesel spill on the energetics of Manila clam (Venerupis philippinarum): Scope for growth and proximate composition in Haíɫzaqv Territory (Central Coast, B.C.) - Tyler Black; Conrad Pilditch; Christopher Kennedy; Diana Chan; Kyle Artelle; Mike Reid; Ryan Prosser (Regional Studies in Marine Science, 2026)

AsPyCC: Post-combustion carbon capture design through Aspen Plus® & Python - Fernando Zea; Christopher Varela; Kyle V. Camarda (Fuel, 2026)

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

The Ibex dune field of Death Valley National Park, California: Characterization and assessment for Use as a Martian analog - Jordan M. Bretzfelder; Mackenzie Day; Marina O. Argueta; Michael R. Zanetti; James R. Zimbelman; BreeAnn Getman; Jacob Widmer; Seulgi Moon; Kyle Miller; Christopher Whetsel (Aeolian Research, 2026)

Using a self-modulated treadmill as a novel approach to study cognitive-motor and biomechanical outcomes during dual-task walking in individuals with and without lower limb loss - Emma P. Shaw; Sarah R. Bass; Jonathan R. Gladish; Kyle Pietro; Alexandra A. Shaver; Christopher Gaskins; Steven Kahl; Christopher L. Dearth; Matthew W. Miller; Alison Pruziner; Bradley D. Hatfield; Brad D. Hendershot; et al. (Experimental Brain Research, 2026)
Combined examination of mental workload and biomechanics during dual-task walking in individuals with lower-limb loss is limited to fixed, but not self-modulated walking pace, for which the latter enables dynamic cognitive-motor behavior as typically engaged during community ambulation. By assessing electroencephalography (EEG) (theta, low/high-alpha power) and biomechanics (gait speed, double limb support, stride width), the cerebral cortical activity underlying mental workload and walking mechanics were examined when individuals with and without lower-limb loss executed a cognitive task (assessed via response time and accuracy) under variable demand (seated and walking). Both populations maintained walking mechanics (unchanged gait speed, double limb support, stride width) during dual-task walking across demand and exhibited similarly elevated neurocognitive engagement (e.g., attention, action monitoring) indicated by similar theta power increase and low/high-alpha power decrease when facing greater demand. However, injured individuals exhibited relative performance decrement (degraded response time/accuracy), which suggests attenuated cognitive-motor efficiency relative to uninjured (i.e., similar cortical activity across groups with degraded performance). Moreover, while uninjured individuals during dual-task walking could robustly engage neurocognitive processes to maintain walking mechanics and successfully attend to the concurrent cognitive task, those with lower-limb loss did not exhibit such a robust recruitment (i.e., unchanged frontal/temporal high-alpha power). Such alterations in individuals with lower-limb loss leads to maintenance of walking at the cost of a concurrent task. The present work informs rehabilitation practice and reveals specific cognitive-motor outcomes for individuals with lower-limb loss in an enhanced ecological context.

Lipids represent a dynamic, yet stable pool of microbially-derived soil carbon - Kaitlin R. Rempfert; Sheryl L. Bell; Christopher P. Kasanke; Jennifer Kyle; Kirsten S. Hofmockel (Soil Biology and Biochemistry, 2026)

FracFeed : Global database of the fraction of feeding predators - Mark Novak; Paige Foust; Shannon Hennessey; Brian P. Tanis; Kyle E. Coblentz; Christopher Wolf; Leah M. Segui; Jeremy S. Henderson; Kurt E. Ingeman; Landon P. Falke; Tamara J. Layden; Daniel J. Gradison; et al. (Ecology, 2026)
The proportion of individuals that are found to have empty stomachs during a survey of a predator population's diet has been used as an indicator of the average individual's state of energy balance and of the degree to which its feeding rate (i.e., its functional response) is saturated with respect to prey availability. As such, the proportion of empty stomachs provides insights into the effects of prey on predators and vice versa, although it is typically unreported in deference to descriptions of the contents of the non‐empty stomachs. The FracFeed database is an ongoing compilation of the proportions of empty and non‐empty stomachs (for gut content surveys) and of feeding and not feeding individuals (for direct observation surveys) reported in publications of predator diet surveys. FracFeed contains data from 4920 diet surveys on 1507 taxa (>4.3 million individuals) spanning cnidarians, ctenophores, chaetognaths, birds, annelids, amphibians, arthropods, mammals, mollusks, reptiles, echinoderms, and fishes that were surveyed in terrestrial, marine, and freshwater ecosystems across the globe over more than 135 years (1887–2023). For most surveys, covariate data include information on the spatial and temporal extent of the diet survey, its central geographical coordinates, the method by which the survey was performed (lethal gut contents, lavage, or direct observation), as well as each predator's standardized taxonomic name and identifier in the Open Tree of Life, its body mass (compiled mostly from independent compilations and additional publications), and its apparent diet's taxonomic richness and resolution. We appeal to more researchers who perform diet surveys to report on the number of empty stomachs they find and encourage additional contributions to the database—particularly from underrepresented geographic regions (e.g., North and Central Asia, North and Central Africa)—to help grow its scope and utility. The database is provided under a CC‐BY‐NC‐S4 4.0 license. Users are requested to cite this data paper when using the data.

Transportation in net-zero emissions futures: Insights from the EMF-37 model intercomparison study - Christopher Hoehne; Matteo Muratori; John Bistline; Carol Lenox; David L. McCollum; Morgan Browning; Kara Podkaminer; Robert H. Beach; Robbie Orvis; Shiqi Ou; Page Kyle; Sharyn Lie; et al. (Energy and Climate Change, 2025)

Bioenergy pathways within United States net-zero CO2 emissions scenarios in the Energy Modeling Forum 37 study - Ronald D. Sands; Liz Wachs; Patrick Lamers; Olivier Bahn; Robert H. Beach; Matthew Binsted; Geoffrey Blanford; Yongxia Cai; Francisco De La Chesnaye; James A. Edmonds; Leonard Göke; Chioke Harris; et al. (Energy and Climate Change, 2025)

Bottom-Use Conflicts in Shallow Coastal Zones: Hard Clam (Mercenaria mercenaria) Aquaculture and Restored Seagrass (Zostera marina) - Grace A. Breitenbeck; Carey J. Johnston; David J. Wilcox; Michael L. Pace; Kyle A. Emery; Christopher J. Patrick (Estuaries and Coasts, 2025)
Multiple-use conflicts of the marine benthos (“bottom-use conflicts”) are increasing as humans expand use of the coastal zone. These conflicts necessitate balanced policies that consider the economic and ecological benefits of different bottom uses. In the Virginia coastal lagoons on the US east coast, there is a potential bottom-use conflict between hard clam ( Mercenaria mercenaria ) aquaculture and seagrass ( Zostera marina ) meadows. We leveraged two decades (2001–2021) of aerial imagery and environmental data to quantify historic trends in bottom use, assess the realized niche of seagrass and clam aquaculture across depth, sand fraction, root mean square (RMS) velocity, fetch, and sea surface temperature (SST) anomaly, and used random forest models to predict the potential extent of seagrass, clam aquaculture, and bottom-use conflict. We found growth in the coverage of both seagrass (+ 3373%) and clam aquaculture (+ 140%) over the past 20 years with a corresponding increase in bottom-use conflict (+ 2579%), though conflict area remained relatively minor. Seagrass occurred in deeper areas with higher fetch, a higher frequency of SST anomalies, lower sand fraction, and similar RMS velocities to areas containing clam aquaculture. Our random forest models predicted potential for the expansion of seagrass (+ 62%) and clam aquaculture (+ 263.9%) with a relatively small area of predicted spatial overlap (12.3%) under current conditions. These results illustrate how species distribution models can help us understand the spatial impacts of aquaculture on natural ecosystems and inform managers and policy makers to create objective policies that balance socioeconomic and ecologic needs.

One for all and all for one health: Harmonizing SARS-CoV-2 wastewater surveillance results across a laboratory network - Alex H.S. Chik; Christopher Adam; Jane J.Y. Ho; Taylor Aris; Eric J. Arts; R. Stephen Brown; David Bulir; Ryland Corchis-Scott; Christopher T. DeGroot; Robert Delatolla; Philip Dennis; Hadi A. Dhiyebi; et al. (Science of The Total Environment, 2025)

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

Reuse of spent granular activated carbon for PFAS removal following hydrothermal alkaline treatment - Ori Soker; Bahareh Tajdini; Angela Abarca-Perez; Aaditi Wadia; Christopher Bellona; Shilai Hao; Kyle Doudrick; Timothy J. Strathmann (Water Research, 2025)

Swine production intensity and swine-specific fecal contamination of household surfaces at residences of industrial livestock operation workers and community residents, North Carolina, USA - Kathleen M. Kurowski; Nora Pisanic; Kristoffer Spicer; Kate Kruczynski; Carolyn Gigot; Devon J. Hall; Devon J. Hall; Kyle T. Aune; Bonita Salmerón; Ana M. Rule; Christopher D. Heaney (Science of The Total Environment, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Historical increases in plant density increased vegetative maize biomass while breeding increased reproductive biomass and allocation to ear over stem - Ezequiel Saenz; Alejo Ruiz; Cintia Sciarresi; Kyle King; Mitchell Baum; Antonella Ferela; Gerasimos J.N. Danalatos; Brenda Gambin; George Kalogeropoulos; August Thies; Raziel A. Ordóñez; Slobodan Trifunovic; et al. (Field Crops Research, 2025)

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Changing climate and disturbance effects on southwestern US forests - Matthew D. Hurteau; Reese Baker; Kyle Gonterman; Abigail Granath; Josh Lopez-Binder; M. Dylan Taylor; Lorraina S. Rojas; Lindsey Rotche; Andy Graves; Marissa J. Goodwin; Gavin Jones; Christopher Marsh (Forest Ecology and Management, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Site‐Specific Nutrient Data Reveal the Importance of Soils in Driving the Mycorrhizal Make‐Up of Woody Vegetation Worldwide - Xiaobin Hua; Christopher H. Lusk; Ian A. Dickie; Stephen Adu‐Bredu; Kathryn J. Allen; Viviana Araus; Laurent Augusto; Pavel Barsukov; David Bauman; Félix Brédoire; David F. R. P. Burslem; James W. Dalling; et al. (Global Ecology and Biogeography, 2025)
Aim Arbuscular mycorrhizas (AM) and ectomycorrhizas (ECM) have different impacts on nutrient cycling, carbon storage, community dynamics and enhancement of photosynthesis by rising CO 2 . Recent global analyses have concluded that patterns of AM/ECM dominance in forests worldwide are shaped by climate, with soil nutrients contributing negligible additional explanatory power. However, their reliance on nutrient data from GIS surfaces masks important local influences of parent material, topography and soil age on soil nutrient status. We asked if use of site‐specific nutrient data reveals a more important role for nutrients. Time Period Present day. Location Global dataset comprising 703 sites, encompassing forests, savanna/woodlands, shrublands and deserts on all continents except Antarctica. Taxa Studied Arborescent plants, including angiosperms, gymnosperms and tree ferns. Methods Generalised Additive Models for Location, Scale and Shape (GAMLSS) to determine the effects of climate variables, soil nitrogen and soil phosphorus on the proportional representation of ECM and of non‐mycorrhizal species (NM) in woody vegetation. Results GAMLSS showed a strong negative relationship of ECM representation with mean annual temperature (MAT), and a strong negative relationship with soil total nitrogen. NM representation was highest on dry sites and phosphorus‐poor sites. Reanalysis showed that GIS‐derived soil nutrient data had less explanatory power than site‐specific nutrient data, and resulted in poorer model fits. Conclusions Our results support the long‐held belief that soil nutrients as well as climate influence the relative fitness of different mycorrhizal syndromes worldwide, and demonstrate the value of using site‐specific nutrient data. Soil nutrients should be considered when predicting the impact of climate change on the mycorrhizal composition of vegetation and resulting shifts in ecosystem processes.

A Functional Response in Resource Selection Links Multiscale Responses of a Large Carnivore to Human Mortality Risk - Kyle D. Dougherty; Justin A. Dellinger; Bogdan Cristescu; Daniel J. Gammons; David K. Garcelon; J. Mark Higley; Quinton E. Martins; Seth P. D. Riley; Jeff A. Sikich; Thomas R. Stephenson; T. Winston Vickers; Greta M. Wengert; et al. (Ecology Letters, 2025)
Theory suggests that animals make hierarchical, multiscale resource selection decisions to address the hierarchy of factors limiting their fitness. Ecologists have developed tools to link population‐level resource selection across scales; yet, theoretical expectations about the relationship between coarse‐ and fine‐scale selection decisions at the individual level remain elusive despite their importance to fitness. With GPS‐telemetry data collected across California, USA, we evaluated resource selection of mountain lions ( Puma concolor ; n = 244) relative to spatial variation in human‐caused mortality risk. With hierarchical resource selection, coarse‐scale selection determines availability at finer scales. This simple relationship allowed us to demonstrate that functional responses in resource selection explicitly link individual‐level resource selection decisions across scales. We show that individuals proactively avoiding risk when selecting home ranges are freed to relax this avoidance when making decisions within home ranges. However, individuals also exhibit reactive avoidance of risk at the finest scales along movement paths.

Controls on spatial variation in porewater methane concentrations across United States tidal wetlands - Erika L. Koontz; Sarah M. Parker; Alice E. Stearns; Brian J. Roberts; Caitlin M. Young; Lisamarie Windham-Myers; Patricia Y. Oikawa; J. Patrick Megonigal; Genevieve L. Noyce; Edward J. Buskey; R. Kyle Derby; Robert P. Dunn; et al. (Science of The Total Environment, 2024)

Climatic drought and trophic disruption in an endemic subalpine Hawaiian forest bird - Kyle S. Van Houtan; Tyler O. Gagné; Paul Banko; Molly E. Hagemann; Robert W. Peck; Christopher T. Yarnes (Biological Conservation, 2024)

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

In vitro endocrine and cardiometabolic toxicity associated with artificial turf materials - Kyle R. Siegel; Brooklynn R. Murray; Jeff Gearhart; Christopher D. Kassotis (Environmental Toxicology and Pharmacology, 2024)

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Home range overlaps of the brushtail possum (Trichosurus vulpecula): implications for disease transmission - Jorge Tobajas; Kyle S. Richardson; Nigel P. French; Bryce Buddle; Christopher Jewell; Daniel M. Tompkins; Carlos Rouco (European Journal of Wildlife Research, 2024)
Understanding how bovine tuberculosis (TB) is maintained in wildlife reservoirs is critical for the management of this disease impacting cattle in many countries. For the primary wildlife reservoir of the disease in New Zealand, the brushtail possum ( Trichosurus vulpecula ), transmission of this contagious bacterial disease among possums is often assumed to be linked to home range overlap. Identifying drivers of possum home range, and home range overlap between individuals, is thus important for informing wildlife reservoir TB management in New Zealand. We monitored four sub-populations of free-living possums in New Zealand native forests during 10 consecutive months using live trapping, to give the first direct insight into how the frequency and area of overlaps alters with density, sex and age. A total of 832 individuals were captured (average 9.3, range from 1 to 40 captures per animal with a median value of 7) and 35,820 home range overlaps were recorded. Both the number and area of overlaps were significantly associated with age class, with 66.6% of overlaps occurring between adults, 30% between adults and juveniles, and only 3.4% between juveniles. Overall, adult males showed significantly higher numbers of overlaps than expected, while adult and juvenile females showed significantly lower numbers of overlaps than expected and no differences were observed in juvenile males. In addition, males exhibited more and larger overlaps than females. The number and size of overlaps per individual decreased with increasing local population density. Understanding shared areas of activity among individuals can provide insights into the interactions occurring and potential pathways for diseases transmitted by contact such as TB. These results can inform to develop effective strategies for the control of diseases carried and dispersed by possums.

Evolution of white matter hyperintensity segmentation methods and implementation over the past two decades; an incomplete shift towards deep learning - Maryam Rahmani; Donna Dierker; Lauren Yaeger; Andrew Saykin; Patrick H. Luckett; Andrei G. Vlassenko; Christopher Owens; Hussain Jafri; Kyle Womack; Jurgen Fripp; Ying Xia; Duygu Tosun; et al. (Brain Imaging and Behavior, 2024)
This systematic review examines the prevalence, underlying mechanisms, cohort characteristics, evaluation criteria, and cohort types in white matter hyperintensity (WMH) pipeline and implementation literature spanning the last two decades. Following Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guidelines, we categorized WMH segmentation tools based on their methodologies from January 1, 2000, to November 18, 2022. Inclusion criteria involved articles using openly available techniques with detailed descriptions, focusing on WMH as a primary outcome. Our analysis identified 1007 visual rating scales, 118 pipeline development articles, and 509 implementation articles. These studies predominantly explored aging, dementia, psychiatric disorders, and small vessel disease, with aging and dementia being the most prevalent cohorts. Deep learning emerged as the most frequently developed segmentation technique, indicative of a heightened scrutiny in new technique development over the past two decades. We illustrate observed patterns and discrepancies between published and implemented WMH techniques. Despite increasingly sophisticated quantitative segmentation options, visual rating scales persist, with the SPM technique being the most utilized among quantitative methods and potentially serving as a reference standard for newer techniques. Our findings highlight the need for future standards in WMH segmentation, and we provide recommendations based on these observations.

Transient, context‐dependent fitness costs accompanying viral resistance in isolates of the marine microalga Micromonas sp. (class Mamiellophyceae) - Anamica Bedi de Silva; Shawn W. Polson; Christopher R. Schvarcz; Grieg F. Steward; Kyle F. Edwards (Environmental Microbiology, 2024)
Marine microbes are important in biogeochemical cycling, but the nature and magnitude of their contributions are influenced by their associated viruses. In the presence of a lytic virus, cells that have evolved resistance to infection have an obvious fitness advantage over relatives that remain susceptible. However, susceptible cells remain extant in the wild, implying that the evolution of a fitness advantage in one dimension (virus resistance) must be accompanied by a fitness cost in another dimension. Identifying costs of resistance is challenging because fitness is context‐dependent. We examined the context dependence of fitness costs in isolates of the picophytoplankton genus Micromonas and their co‐occurring dsDNA viruses using experimental evolution. After generating 88 resistant lineages from two ancestral Micromonas strains, each challenged with one of four distinct viral strains, we found resistance led to a 46% decrease in mean growth rate under high irradiance and a 19% decrease under low. After a year in culture, the experimentally selected lines remained resistant, but fitness costs had attenuated. Our results suggest that the cost of resistance in Micromonas is dependent on environmental conditions and the duration of population adaptation, illustrating the dynamic nature of fitness costs of viral resistance among marine protists.

SNAPSHOT USA 2021: A third coordinated national camera trap survey of the U nited S tates - Hila Shamon; Roi Maor; Michael V. Cove; Roland Kays; Jessie Adley; Peter D. Alexander; David N. Allen; Maximilian L. Allen; Cara L. Appel; Evan Barr; Erika L. Barthelmess; Carolina Baruzzi; et al. (Ecology, 2024)
SNAPSHOT USA is a multicontributor, long‐term camera trap survey designed to survey mammals across the United States. Participants are recruited through community networks and directly through a website application ( https://www.snapshot-usa.org/ ). The growing Snapshot dataset is useful, for example, for tracking wildlife population responses to land use, land cover, and climate changes across spatial and temporal scales. Here we present the SNAPSHOT USA 2021 dataset, the third national camera trap survey across the US. Data were collected across 109 camera trap arrays and included 1711 camera sites. The total effort equaled 71,519 camera trap nights and resulted in 172,507 sequences of animal observations. Sampling effort varied among camera trap arrays, with a minimum of 126 camera trap nights, a maximum of 3355 nights, a median 546 nights, and a mean 656 ± 431 nights. This third dataset comprises 51 camera trap arrays that were surveyed during 2019, 2020, and 2021, along with 71 camera trap arrays that were surveyed in 2020 and 2021. All raw data and accompanying metadata are stored on Wildlife Insights ( https://www.wildlifeinsights.org/ ), and are publicly available upon acceptance of the data papers. SNAPSHOT USA aims to sample multiple ecoregions in the United States with adequate representation of each ecoregion according to its relative size. Currently, the relative density of camera trap arrays varies by an order of magnitude for the various ecoregions (0.22–5.9 arrays per 100,000 km 2 ), emphasizing the need to increase sampling effort by further recruiting and retaining contributors. There are no copyright restrictions on these data. We request that authors cite this paper when using these data, or a subset of these data, for publication. Any use of trade, firm, or product names is for descriptive purposes only and does not imply endorsement by the US Government.

A brief history of the thermal IR-based Two-Source Energy Balance (TSEB) model – diagnosing evapotranspiration from plant to global scales - Martha C. Anderson; William P. Kustas; John M. Norman; George T. Diak; Christopher R. Hain; Feng Gao; Yun Yang; Kyle R. Knipper; Jie Xue; Yang Yang; Wade T. Crow; Thomas R.H. Holmes; et al. (Agricultural and Forest Meteorology, 2024)

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Calling up ghosts: acoustic playback of social vocalisations reveals complex communication in a cryptic bat and provides a promising tool for monitoring disturbance-sensitive species - Nicola Hanrahan; Christopher Turbill; Anastasia H. Dalziell; Kyle N. Armstrong; Justin A. Welbergen (Mammal Research, 2024)

Co-Production of Knowledge at Sumida Farm Trains a New Generation of Community-Engaged Scientists - Jennifer Engels; Barbara Bruno; Emi Suzuki; Kyle Suzuki; Henrietta Dulai; Mackenzie Manning; Donn Viviani; Kekuʻiapōiula Keliipuleole; Brandon Dela Cruz; Kathy Ho; Kyle Kila; Tehani Malterre; et al. (Oceanography, 2024)
The Sumida watercress farm near Pu‘uloa (Pearl Harbor), O‘ahu has been in continuous operation since 1928. This family-run farm (Figure 1a) produces 70% of the state’s watercress crop, making it critical to Hawai‘i’s food production. The farm’s watercress relies completely on water from freshwater springs. However, the amount of water flowing from the springs has declined by half over the last century as a result of groundwater pumping, climate change, and other drivers (Oki, 2005). Mo‘olelo (oral histories) published in Hawaiian language newspapers from 1834 to 1948 document the springs’ use for agriculture and recreation by Hawaiian ali‘i (chiefs) for more than 1,000 years (Engels et al., 2020).

Thirty‐six years of butterfly monitoring, snow cover, and plant productivity reveal negative impacts of warmer winters and increased productivity on montane species - Christopher A. Halsch; Arthur M. Shapiro; James H. Thorne; Kyle C. Rodman; Adriana Parra; Lee A. Dyer; Zachariah Gompert; Angela M. Smilanich; Matthew L. Forister (Global Change Biology, 2024)
Climate change is contributing to declines of insects through rising temperatures, altered precipitation patterns, and an increasing frequency of extreme events. The impacts of both gradual and sudden shifts in weather patterns are realized directly on insect physiology and indirectly through impacts on other trophic levels. Here, we investigated direct effects of seasonal weather on butterfly occurrences and indirect effects mediated by plant productivity using a temporally intensive butterfly monitoring dataset, in combination with high‐resolution climate data and a remotely sensed indicator of plant primary productivity. Specifically, we used Bayesian hierarchical path analysis to quantify relationships between weather and weather‐driven plant productivity on the occurrence of 94 butterfly species from three localities distributed across an elevational gradient. We found that snow pack exerted a strong direct positive effect on butterfly occurrence and that low snow pack was the primary driver of reductions during drought. Additionally, we found that plant primary productivity had a consistently negative effect on butterfly occurrence. These results highlight mechanisms of weather‐driven declines in insect populations and the nuances of climate change effects involving snow melt, which have implications for ecological theories linking topographic complexity to ecological resilience in montane systems.

Biomass burning in the Neotropics is exposing migrating birds to elevated fine particulate matter concentrations - Frank A. La Sorte; Benjamin Zuckerberg; Christopher A. Lepczyk; Myla F. J. Aronson; Kyle G. Horton (Global Ecology and Biogeography, 2023)
Aim A unique risk faced by nocturnally migrating birds is the disorienting influence of artificial light at night (ALAN). ALAN originates from anthropogenic activities that can generate other forms of environmental pollution, including the emission of fine particulate matter (PM 2.5 ). PM 2.5 concentrations can display strong seasonal variation whose origin can be natural or anthropogenic. How this variation affects seasonal associations with ALAN and PM 2.5 for nocturnally migrating bird populations has not been explored. Location Western Hemisphere. Time Period 2021 Major Taxa Studied Nocturnally migrating passerine (NMP) bird species. Methods We combined monthly estimates of PM 2.5 and ALAN with weekly estimates of relative abundance for 164 NMP species derived using observations from eBird. We identified groups of species with similar associations with monthly PM 2.5 . We summarized their shared environmental, geographical, and ecological attributes. Results PM 2.5 was lowest in North America, especially at higher latitudes during the boreal winter. PM 2.5 was highest in the Amazon Basin, especially during the dry season (August–October). ALAN was highest within eastern North America, especially during the boreal winter. For NMP species, PM 2.5 associations reached their lowest levels during the breeding season ( 3 ) and highest levels during the nonbreeding season, especially for long‐distance migrants that winter in Central and South America (~20 μg/m 3 ). Species that migrate through Central America in the spring encountered similarly high PM 2.5 concentrations. ALAN associations reached their highest levels for species that migrate (~12 nW/cm 2 /sr) or spend the nonbreeding season (~15 nW/cm 2 /sr) in eastern North America. Main Conclusions We did not find evidence that the disorienting influence of ALAN enhances PM 2.5 exposure during stopover in the spring and autumn for NMP species. Rather, our findings suggest biomass burning in the Neotropics is exposing NMP species to consistently elevated PM 2.5 concentrations for an extended period of their annual life cycles.

Dynamics of the Apostichopus californicus-associated flavivirus under suboxic conditions and organic matter amendment - Jameson G. Crandell; Ashley K. Altera; Christopher M. DeRito; Kyle P. Hebert; Em G. Lim; Joel Markis; Katherine H. Philipp; Jordan E. Rede; Megan Schwartz; Brayan Vilanova-Cuevas; Evangeline Wang; Ian Hewson (Frontiers in Marine Science, 2023)
Flaviviruses cause some of the most detrimental vertebrate diseases, yet little is known of their impacts on invertebrates. Microbial activities at the animal-water interface are hypothesized to influence viral replication and possibly contribute to pathology of echinoderm wasting diseases due to hypoxic stress. We assessed the impacts of enhanced microbial production and suboxic stress on Apostichopus californicus associated flavivirus (PcaFV) load in a mesocosm experiment. Organic matter amendment and suboxic stress resulted in lower PcaFV load, which also correlated negatively with animal mass loss and microbial activity at the animal-water interface. These data suggest that PcaFV replication and persistence was best supported in healthier specimens. Our results do not support the hypothesis that suboxic stress or microbial activity promote PcaFV replication, but rather that PcaFV appears to be a neutral or beneficial symbiont of Apostichopus californicus .

Processing municipal solid waste incineration bottom ash for integration into cement product manufacture - Jordan K. Magnuson; Kate D. Weiksnar; Ashish D. Patel; Kyle A. Clavier; Christopher C. Ferraro; Timothy G. Townsend (Resources, Conservation and Recycling, 2023)

Impact of fixture purging on water age and excess water usage, considering stochastic water demands - Emily Clements; Christopher Irwin; Alexandros Taflanidis; Kyle Bibby; Robert Nerenberg (Water Research, 2023)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

Pre‐adaptation and adaptation shape trait‐environment matching in the Neotropics - Francisco J. Velásquez‐Puentes; Benjamin M. Torke; Christopher D. Barratt; Kyle G. Dexter; Toby Pennington; Flávia Fonseca Pezzini; Alexander Zizka; Renske E. Onstein (Global Ecology and Biogeography, 2023)
Aim Functional traits shape the distribution of taxa across environments. However, it remains unclear whether trait and environmental niche evolution are correlated, and what happened first: trait change facilitating environment shifts (pre‐adaptation) or environmental change leading to trait change (adaptation). We focus on a species‐rich Neotropical legume radiation to shed light on this enigma. Location Neotropics. Time Period Cenozoic. Major Taxa Studied Fabaceae: Papilionoidae: Swartzia . Methods We assembled leaflet, fruit and petal size data from monographs and herbarium collections for 86 to 96% of the c. 180 Swartzia species, inferred a dated Swartzia phylogenetic tree from existing DNA sequences covering 38% of the species and integrated these with distribution, soil and climate data. We used phylogenetic linear regression to quantify trait–environment relationships and applied comparative methods to evaluate modes of correlated evolution between traits and environments. Results Leaflet and petal size were strongly linked to climate, while fruit size was not associated with climate or soil characteristics. Evolutionary transitions to relatively low rainfall and low temperature environments were conditional on the evolution of small leaflets, whereas transitions to wet and warm environments were preceded by the evolution of larger leaflets. In contrast, transitions to the warmest or coldest environments were followed, rather than preceded, by petal loss. Main Conclusion Our results show that the macroevolution of functional traits has influenced the broad‐scale distribution of Swartzia across Neotropical rainforest, seasonally dry, montane and inundated habitats. We suggest that trait evolution is conditional on environmental change but both pre‐adaptive and adaptive processes may occur. These processes are important to understand the distribution of diversity at both regional (e.g. Amazonia) and global biogeographical scales.

Harvest index has increased over the last 50 years of maize breeding - Alejo Ruiz; Slobodan Trifunovic; Douglas M. Eudy; Cintia S. Sciarresi; Mitchell Baum; Gerasimos J.N. Danalatos; Elvis F. Elli; Georgios Kalogeropoulos; Kyle King; Caio dos Santos; August Thies; Lia Olmedo Pico; et al. (Field Crops Research, 2023)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Rapidly Changing Range Limits in a Warming World: Critical Data Limitations and Knowledge Gaps for Advancing Understanding of Mangrove Range Dynamics in the Southeastern USA - Rémi Bardou; Michael J. Osland; Steven Scyphers; Christine Shepard; Karen E. Aerni; Jahson B. Alemu I; Robert Crimian; Richard H. Day; Nicholas M. Enwright; Laura C. Feher; Sarah L. Gibbs; Kiera O’Donnell; et al. (Estuaries and Coasts, 2023)
Climate change is altering species’ range limits and transforming ecosystems. For example, warming temperatures are leading to the range expansion of tropical, cold-sensitive species at the expense of their cold-tolerant counterparts. In some temperate and subtropical coastal wetlands, warming winters are enabling mangrove forest encroachment into salt marsh, which is a major regime shift that has significant ecological and societal ramifications. Here, we synthesized existing data and expert knowledge to assess the distribution of mangroves near rapidly changing range limits in the southeastern USA. We used expert elicitation to identify data limitations and highlight knowledge gaps for advancing understanding of past, current, and future range dynamics. Mangroves near poleward range limits are often shorter, wider, and more shrublike compared to their tropical counterparts that grow as tall forests in freeze-free, resource-rich environments. The northern range limits of mangroves in the southeastern USA are particularly dynamic and climate sensitive due to abundance of suitable coastal wetland habitat and the exposure of mangroves to winter temperature extremes that are much colder than comparable range limits on other continents. Thus, there is need for methodological refinements and improved spatiotemporal data regarding changes in mangrove structure and abundance near northern range limits in the southeastern USA. Advancing understanding of rapidly changing range limits is critical for foundation plant species such as mangroves, as it provides a basis for anticipating and preparing for the cascading effects of climate-induced species redistribution on ecosystems and the human communities that depend on their ecosystem services.

Corrigendum to “Quantifying annual spatial consistency in chick-rearing seabirds to inform important site identification” [Biol. Conserv. 281 (2023) 109994] - Martin Beal; Paulo Catry; Richard A. Phillips; Steffen Oppel; John P.Y. Arnould; Maria I. Bogdanova; Mark Bolton; Ana P.B. Carneiro; Corey Clatterbuck; Melinda Conners; Francis Daunt; Karine Delord; et al. (Biological Conservation, 2023)

Quantifying annual spatial consistency in chick-rearing seabirds to inform important site identification - Martin Beal; Paulo Catry; Richard A. Phillips; Steffen Oppel; John P.Y. Arnould; Maria I. Bogdanova; Mark Bolton; Ana P.B. Carneiro; Corey Clatterbuck; Melinda Conners; Francis Daunt; Karine Delord; et al. (Biological Conservation, 2023)

Development of a Benchmark Eddy Flux Evapotranspiration Dataset for Evaluation of Satellite-Driven Evapotranspiration Models Over the CONUS - John M. Volk; Justin Huntington; Forrest S. Melton; Richard Allen; Martha C. Anderson; Joshua B. Fisher; Ayse Kilic; Gabriel Senay; Gregory Halverson; Kyle Knipper; Blake Minor; Christopher Pearson; et al. (Agricultural and Forest Meteorology, 2023)

Variation in organic matter across the Cretaceous-Paleogene boundary in New Zealand supports the “Living Ocean” model of biotic recovery - Claudia Sosa-Montes de Oca; Kyle W.R. Taylor; Christopher J. Hollis; Yizhou Huang; Richard D. Pancost (Global and Planetary Change, 2023)

Degradation of microcystin algal toxin by 3D printable polymer immobilized photocatalytic TiO2 - Alan J. Kennedy; Andrew D. McQueen; Mark L. Ballentine; Lauren R. May; Brianna M. Fernando; Arit Das; Kyle L. Klaus; Christopher B. Williams; Michael J. Bortner (Chemical Engineering Journal, 2023)

Improving the spatiotemporal resolution of remotely sensed ET information for water management through Landsat, Sentinel-2, ECOSTRESS and VIIRS data fusion - Jie Xue; Martha C. Anderson; Feng Gao; Christopher Hain; Kyle R. Knipper; Yun Yang; William P. Kustas; Yang Yang; Nicolas Bambach; Andrew J. McElrone; Sebastian J. Castro; Joseph G. Alfieri; et al. (Irrigation Science, 2022)
Robust information on consumptive water use (evapotranspiration, ET) derived from remote sensing can significantly benefit water decision-making in agriculture, informing irrigation schedules and water management plans over extended regions. To be of optimal utility for operational usage, these remote sensing ET data should be generated at the sub-field spatial resolution and daily-to-weekly timesteps commensurate with the scales of water management activities. However, current methods for field-scale ET retrieval based on thermal infrared (TIR) imaging, a valuable diagnostic of canopy stress and surface moisture status, are limited by the temporal revisit of available medium-resolution (100 m or finer) thermal satellite sensors. This study investigates the efficacy of a data fusion method for combining information from multiple medium-resolution sensors toward generating high spatiotemporal resolution ET products for water management. TIR data from Landsat and ECOSTRESS (both at ~ 100-m native resolution), and VIIRS (375-m native) are sharpened to a common 30-m grid using surface reflectance data from the Harmonized Landsat-Sentinel dataset. Periodic 30-m ET retrievals from these combined thermal data sources are fused with daily retrievals from unsharpened VIIRS to generate daily, 30-m ET image timeseries. The accuracy of this mapping method is tested over several irrigated cropping systems in the Central Valley of California in comparison with flux tower observations, including measurements over irrigated vineyards collected in the GRAPEX campaign. Results demonstrate the operational value added by the augmented TIR sensor suite compared to Landsat alone, in terms of capturing daily ET variability and reduced latency for real-time applications. The method also provides means for incorporating new sources of imaging from future planned thermal missions, further improving our ability to map rapid changes in crop water use at field scales.

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Potential biomarkers of endocrine and habitat disruption identified via RNA-Seq in Salvelinus fontinalis with proximity to fracking operations in Pennsylvania headwater stream ecosystems - Christopher J. McLimans; Katharine Shelledy; William Conrad; Kyle Prendergast; Anh N. Le; Christopher J. Grant; Vincent P. Buonaccorsi (Ecotoxicology, 2022)

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Globally, tree fecundity exceeds productivity gradients - Valentin Journé; Robert Andrus; Marie‐Claire Aravena; Davide Ascoli; Roberta Berretti; Daniel Berveiller; Michal Bogdziewicz; Thomas Boivin; Raul Bonal; Thomas Caignard; Rafael Calama; Jesús Julio Camarero; et al. (Ecology Letters, 2022)
Lack of tree fecundity data across climatic gradients precludes the analysis of how seed supply contributes to global variation in forest regeneration and biotic interactions responsible for biodiversity. A global synthesis of raw seedproduction data shows a 250‐fold increase in seed abundance from cold‐dry to warm‐wet climates, driven primarily by a 100‐fold increase in seed production for a given tree size. The modest (threefold) increase in forest productivity across the same climate gradient cannot explain the magnitudes of these trends. The increase in seeds per tree can arise from adaptive evolution driven by intense species interactions or from the direct effects of a warm, moist climate on tree fecundity. Either way, the massive differences in seed supply ramify through food webs potentially explaining a disproportionate role for species interactions in the wet tropics.

Assessing the combined threats of artificial light at night and air pollution for the world’s nocturnally migrating birds - Frank A. La Sorte; Myla F. J. Aronson; Christopher A. Lepczyk; Kyle G. Horton (Global Ecology and Biogeography, 2022)
Aim Two important environmental hazards for nocturnally migrating birds are artificial light at night (ALAN) and air pollution, with ambient fine particulate matter (PM 2.5 ) considered to be especially harmful. Nocturnally migrating birds are attracted to ALAN during seasonal migration, which could increase exposure to PM 2.5 . Here, we examine PM 2.5 concentrations and PM 2.5 trends and the spatial correlation between ALAN and PM 2.5 within the geographical ranges of the world’s nocturnally migrating birds. Location Global. Time period 1998–2018. Major taxa studied Nocturnally migrating birds. Methods We intersected a global database of annual mean PM 2.5 concentrations over a 21‐year period (1998–2018) with the geographical ranges (breeding, non‐breeding and regions of passage) of 225 nocturnally migrating bird species in three migration flyways (Americas, n = 143; Africa–Europe, n = 36; and East Asia–Australia, n = 46). For each species, we estimated PM 2.5 concentrations and trends and measured the correlation between ALAN and PM 2.5 , which we summarized by season and flyway. Results Correlations between ALAN and PM 2.5 were significantly positive across all seasons and flyways. The East Asia–Australia flyway had the strongest ALAN–PM 2.5 correlations within regions of passage, the highest PM 2.5 concentrations across all three seasons and the strongest positive PM 2.5 trends on the non‐breeding grounds and within regions of passage. The Americas flyway had the strongest negative air pollution trends on the non‐breeding grounds and within regions of passage. The breeding grounds had similarly negative air pollution trends within the three flyways. Main conclusions The combined threats of ALAN and air pollution are greatest and likely to be increasing within the East Asia–Australia flyway and lowest and likely to be decreasing within the Americas and Africa–Europe flyways. Reversing PM 2.5 trends in the East Asia–Australia flyway and maintaining negative PM 2.5 trends in the Americas and Africa–Europe flyways while reducing ALAN levels would likely be beneficial for the nocturnally migrating bird populations in each region.

Swine models for translational oncological research: an evolving landscape and regulatory considerations - Adeline N. Boettcher; Kyle M. Schachtschneider; Lawrence B. Schook; Christopher K. Tuggle (Mammalian Genome, 2022)

COVID-19-associated necrotizing encephalopathy presenting without active respiratory symptoms: a case report with histopathology - Leigh A. Rettenmaier; Lama Abdel-Wahed; Hisham Abdelmotilib; Kyle S. Conway; Nandakumar Narayanan; Christopher L. Groth (Journal of NeuroVirology, 2022)

Evaluation of the Effectiveness of Newer Helmet Designs with Emergent Shell and Padding Technologies Versus Older Helmet Models for Preserving White Matter Following a Season of High School Football - Jed A. Diekfuss; Weihong Yuan; Jonathan A. Dudley; Christopher A. DiCesare; Matthew B. Panzer; Thomas M. Talavage; Eric Nauman; Scott Bonnette; Alexis B. Slutsky-Ganesh; Joseph Clark; Manish Anand; Mekibib Altaye; et al. (Annals of Biomedical Engineering, 2021)

Four decades of reef observations illuminate deep‐water grouper hotspots - Avery B. Paxton; Stacey L. Harter; Steve W. Ross; Christina M. Schobernd; Brendan J. Runde; Paul J. Rudershausen; Katrina H. Johnson; Kyle W. Shertzer; Nathan M. Bacheler; Jeffrey A. Buckel; G. Todd Kellison; J. Christopher Taylor (Fish and Fisheries, 2021)
Fish often aggregate to spawn, feed, rest, or avoid predation. Direct observations of very high counts of large‐bodied grouper on deep shipwrecks, however, do not fit into typical descriptions of spawning‐, resource‐, or predation‐driven aggregations. To investigate whether these observations are rare or part of an underlying pattern, we synthesized four decades (1979–2019) of direct observations of groupers on deep‐water (50–300 m) habitats along the southeastern United States (Cape Hatteras, NC to Cape Canaveral, FL). The direct observations, which included 439 remotely operated vehicle transects, 235 human‐occupied vehicle transects, and 881 hook‐and‐line drops, revealed six hotspots of deep‐water groupers on three shipwrecks, two artificial reefs, and one boulder field. Grouper counts at these hotspots (0.10–5.40 grouper per linear m surveyed) exceeded counts of grouper outside of hotspots (

Sex differences in changes of protein synthesis with rapamycin treatment are minimized when metformin is added to rapamycin - Christopher A. Wolff; Marcus M. Lawrence; Hunter Porter; Qian Zhang; Justin J. Reid; Jaime L. Laurin; Robert V. Musci; Melissa A. Linden; Frederick F. Peelor; Jonathan D. Wren; Joseph S. Creery; Kyle J. Cutler; et al. (GeroScience, 2021)

Making sense of virus size and the tradeoffs shaping viral fitness - Kyle F. Edwards; Grieg F. Steward; Christopher R. Schvarcz (Ecology Letters, 2021)
Viruses span an impressive size range, with genome length varying a thousandfold and virion volume nearly a millionfold. For cellular organisms the scaling of traits with size is a pervasive influence on ecological processes, but whether size plays a central role in viral ecology is unknown. Here, we focus on viruses of aquatic unicellular organisms, which exhibit the greatest known range of virus size. We outline hypotheses within a quantitative framework, and analyse data where available, to consider how size affects the primary components of viral fitness. We argue that larger viruses have fewer offspring per infection and slower contact rates with host cells, but a larger genome tends to increase infection efficiency, broaden host range, and potentially increase attachment success and decrease decay rate. These countervailing selective pressures may explain why a breadth of sizes exist and even coexist when infecting the same host populations. Oligotrophic ecosystems may be enriched in “giant” viruses, because environments with resource‐limited phagotrophs at low concentrations may select for broader host range, better control of host metabolism, lower decay rate and a physical size that mimics bacterial prey. Finally, we describe where further research is needed to understand the ecology and evolution of viral size diversity.

Plasticity in the grazing ecophysiology of Florenciella (Dichtyochophyceae), a mixotrophic nanoflagellate that consumes Prochlorococcus and other bacteria - Qian Li; Kyle F. Edwards; Christopher R. Schvarcz; Karen E. Selph; Grieg F. Steward (Limnology and Oceanography, 2021)
Mixotrophic nanoflagellates can account for more than half of the bacterivory in the sunlit ocean, yet very little is known about their ecophysiology. Here, we characterize the grazing ecology of an open‐ocean mixotroph in the genus Florenciella (class Dictyochophyceae). Members of this class were indirectly implicated as major consumers of Prochlorococcus and Synechococcus in the oligotrophic North Pacific Subtropical Gyre, but their phagotrophic capabilities have never been investigated. Our studies showed that Florenciella readily consumed Prochlorococcus , Synechococcus , and heterotrophic bacteria, and that the ingested prey relieved nutrient limitations on growth. Florenciella grew faster (3 d −1 ) in nitrogen‐deplete medium given sufficient live Synechococcus , than in nitrogen‐replete K medium (2 d −1 ), but it did not grow in continuous darkness. Grazing rates were substantially higher under nutrient limitation and showed a hint of diel variability, with rates tending to be highest near the end of the light period. An apparent trade‐off between the maximum clearance rate (5 nL Florenciella −1 h −1 ) and the maximum ingestion rate (up to ∼ 10 prey cells Florenciella −1 h −1 ) across experiments suggests that grazing behavior may also vary in response to prey concentration. If the observed grazing rates are representative of other open‐ocean mixotrophs, their collective activity could account for a significant fraction of the daily cyanobacterial mortality. This study provides essential parameters for understanding the grazing ecology of a common marine mixotroph and the first characterization of mixotrophic nanoflagellate functional responses when feeding on unicellular cyanobacteria, the dominant marine primary producers in the oligotrophic ocean.

The Utility of Satellites and Autonomous Remote Sensing Platforms for Monitoring Offshore Aquaculture Farms: A Case Study for Canopy Forming Kelps - Tom W. Bell; Nick J. Nidzieko; David A. Siegel; Robert J. Miller; Kyle C. Cavanaugh; Norman B. Nelson; Daniel C. Reed; Dmitry Fedorov; Christopher Moran; Jordan N. Snyder; Katherine C. Cavanaugh; Christie E. Yorke; et al. (Frontiers in Marine Science, 2020)
The emerging sector of offshore kelp aquaculture represents an opportunity to produce biofuel feedstock to help meet growing energy demand. Giant kelp represents an attractive aquaculture crop due to its rapid growth and production, however precision farming over large scales is required to make this crop economically viable. These demands necessitate high frequency monitoring to ensure outplant success, maximum production, and optimum quality of harvested biomass, while the long distance from shore and large necessary scales of production makes in person monitoring impractical. Remote sensing offers a practical monitoring solution and nascent imaging technologies could be leveraged to provide daily products of the kelp canopy and subsurface structures over unprecedented spatial scales. Here, we evaluate the efficacy of remote sensing from satellites and aerial and underwater autonomous vehicles as potential monitoring platforms for offshore kelp aquaculture farms. Decadal-scale analyses of the Southern California Bight showed that high offshore summertime cloud cover restricts the ability of satellite sensors to provide high frequency direct monitoring of these farms. By contrast, daily monitoring of offshore farms using sensors mounted to aerial and underwater drones seems promising. Small Unoccupied Aircraft Systems (sUAS) carrying lightweight optical sensors can provide estimates of canopy area, density, and tissue nitrogen content on the time and space scales necessary for observing changes in this highly dynamic species. Underwater color imagery can be rapidly classified using deep learning models to identify kelp outplants on a longline farm and high acoustic returns of kelp pneumatocysts from side scan sonar imagery signal an ability to monitor the subsurface development of kelp fronds. Current sensing technologies can be used to develop additional machine learning and spectral algorithms to monitor outplant health and canopy macromolecular content, however future developments in vehicle and infrastructure technologies are necessary to reduce costs and transcend operational limitations for continuous deployment in an offshore setting.

Development of a massively parallel, genotyping-by-sequencing assay in American badger (Taxidea taxus) highlights the need for careful validation when working with low template DNA - Michael E. Donaldson; Katelyn Jackson; Yessica Rico; Josh B. Sayers; Danielle M. Ethier; Christopher J. Kyle (Conservation Genetics Resources, 2020)

Meta-Analysis Reveals Artificial Reefs Can Be Effective Tools for Fish Community Enhancement but Are Not One-Size-Fits-All - Avery B. Paxton; Kyle W. Shertzer; Nathan M. Bacheler; G. Todd Kellison; Kenneth L. Riley; J. Christopher Taylor (Frontiers in Marine Science, 2020)

mGluR5 Allosteric Modulation Promotes Neurorecovery in a 6-OHDA-Toxicant Model of Parkinson’s Disease - Kyle Farmer; Khaled S. Abd-Elrahman; Alexa Derksen; Elyn M. Rowe; Ashley M. Thompson; Christopher A. Rudyk; Natalie A. Prowse; Zachary Dwyer; Samantha C. Bureau; Teresa Fortin; Stephen S.G. Ferguson; Shawn Hayley (Molecular Neurobiology, 2020)

Acute Post-Activation Potentiation Effects of Heavy High-Pulls on Clean Performance - Marisa K. Straughn; Christopher C. Dake; Ludmila M. Cosio-Lima; Cameron D. Addie; Kyle B. Rank; Sarai D. Flores; Lee E. Brown (Journal of Science in Sport and Exercise, 2019)

Lipolytic Activity and the Utilization of Fatty Acids Associated with Bat Sebum by Pseudogymnoascus destructans - Kyle T. Gabriel; John J. Neville; George E. Pierce; Christopher T. Cornelison (Mycopathologia, 2019)

In Vitro Priming and Hyper-Activation of Brain Microglia: an Assessment of Phenotypes - Kyle Koss; Matthew A. Churchward; Christopher Tsui; Kathryn G. Todd (Molecular Neurobiology, 2019)

Comparison of vineyard evapotranspiration estimates from surface renewal using measured and modelled energy balance components in the GRAPEX project - Christopher K. Parry; William P. Kustas; Kyle R. Knipper; Martha C. Anderson; Joseph G. Alfieri; John H. Prueger; Andrew J. McElrone (Irrigation Science, 2019)

Evapotranspiration estimates derived using thermal-based satellite remote sensing and data fusion for irrigation management in California vineyards - Kyle R. Knipper; William P. Kustas; Martha C. Anderson; Joseph G. Alfieri; John H. Prueger; Christopher R. Hain; Feng Gao; Yun Yang; Lynn G. McKee; Hector Nieto; Lawrence E. Hipps; Maria Mar Alsina; et al. (Irrigation Science, 2019)

Genetic source–sink dynamics among naturally structured and anthropogenically fragmented puma populations - Kyle D. Gustafson; Roderick B. Gagne; T. Winston Vickers; Seth P. D. Riley; Christopher C. Wilmers; Vernon C. Bleich; Becky M. Pierce; Marc Kenyon; Tracy L. Drazenovich; Jeff A. Sikich; Walter M. Boyce; Holly B. Ernest (Conservation Genetics, 2019)

Compositional response of Amazon forests to climate change - Adriane Esquivel‐Muelbert; Timothy R. Baker; Kyle G. Dexter; Simon L. Lewis; Roel J. W. Brienen; Ted R. Feldpausch; Jon Lloyd; Abel Monteagudo‐Mendoza; Luzmila Arroyo; Esteban Álvarez-Dávila; Niro Higuchi; Beatriz S. Marimon; et al. (Global Change Biology, 2019)
Most of the planet's diversity is concentrated in the tropics, which includes many regions undergoing rapid climate change. Yet, while climate‐induced biodiversity changes are widely documented elsewhere, few studies have addressed this issue for lowland tropical ecosystems. Here we investigate whether the floristic and functional composition of intact lowland Amazonian forests have been changing by evaluating records from 106 long‐term inventory plots spanning 30 years. We analyse three traits that have been hypothesized to respond to different environmental drivers (increase in moisture stress and atmospheric CO 2 concentrations): maximum tree size, biogeographic water‐deficit affiliation and wood density. Tree communities have become increasingly dominated by large‐statured taxa, but to date there has been no detectable change in mean wood density or water deficit affiliation at the community level, despite most forest plots having experienced an intensification of the dry season. However, among newly recruited trees, dry‐affiliated genera have become more abundant, while the mortality of wet‐affiliated genera has increased in those plots where the dry season has intensified most. Thus, a slow shift to a more dry‐affiliated Amazonia is underway, with changes in compositional dynamics (recruits and mortality) consistent with climate‐change drivers, but yet to significantly impact whole‐community composition. The Amazon observational record suggests that the increase in atmospheric CO 2 is driving a shift within tree communities to large‐statured species and that climate changes to date will impact forest composition, but long generation times of tropical trees mean that biodiversity change is lagging behind climate change.

Antimicrobial Activity of Essential Oils Against the Fungal Pathogens Ascosphaera apis and Pseudogymnoascus destructans - Kyle T. Gabriel; Leila Kartforosh; Sidney A. Crow; Christopher T. Cornelison (Mycopathologia, 2018)

Evolutionarily stable communities: a framework for understanding the role of trait evolution in the maintenance of diversity - Kyle F. Edwards; Colin T. Kremer; Elizabeth T. Miller; Matthew M. Osmond; Elena Litchman; Christopher A. Klausmeier (Ecology Letters, 2018)
Biological diversity depends on the interplay between evolutionary diversification and ecological mechanisms allowing species to coexist. Current research increasingly integrates ecology and evolution over a range of timescales, but our common conceptual framework for understanding species coexistence requires better incorporation of evolutionary processes. Here, we focus on the idea of evolutionarily stable communities ( ESC s), which are theoretical endpoints of evolution in a community context. We use ESC s as a unifying framework to highlight some important but under‐appreciated theoretical results, and we review empirical research relevant to these theoretical predictions. We explain how, in addition to generating diversity, evolution can also limit diversity by reducing the effectiveness of coexistence mechanisms. The coevolving traits of competing species may either diverge or converge, depending on whether the number of species in the community is low (undersaturated) or high (oversaturated) relative to the ESC . Competition in oversaturated communities can lead to extinction or neutrally coexisting, ecologically equivalent species. It is critical to consider trait evolution when investigating fundamental ecological questions like the strength of different coexistence mechanisms, the feasibility of ecologically equivalent species, and the interpretation of different patterns of trait dispersion.

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Quantifying predator dependence in the functional response of generalist predators - Mark Novak; Christopher Wolf; Kyle E. Coblentz; Isaac D. Shepard (Ecology Letters, 2017)
A long‐standing debate concerns how functional responses are best described. Theory suggests that ratio dependence is consistent with many food web patterns left unexplained by the simplest prey‐dependent models. However, for logistical reasons, ratio dependence and predator dependence more generally have seen infrequent empirical evaluation and then only so in specialist predators, which are rare in nature. Here we develop an approach to simultaneously estimate the prey‐specific attack rates and predator‐specific interference (facilitation) rates of predators interacting with arbitrary numbers of prey and predator species in the field. We apply the approach to surveys and experiments involving two intertidal whelks and their full suite of potential prey. Our study provides strong evidence for predator dependence that is poorly described by the ratio dependent model over manipulated and natural ranges of species abundances. It also indicates how, for generalist predators, even the qualitative nature of predator dependence can be prey‐specific.

A global database of nitrogen and phosphorus excretion rates of aquatic animals - Michael J. Vanni; Peter B. McIntyre; Dennis Allen; Diane L. Arnott; Jonathan P. Benstead; David J. Berg; Åge Brabrand; Sébastien Brosse; Paul A. Bukaveckas; Adriano Caliman; Krista A. Capps; Luciana S. Carneiro; et al. (Ecology, 2017)
Animals can be important in modulating ecosystem‐level nutrient cycling, although their importance varies greatly among species and ecosystems. Nutrient cycling rates of individual animals represent valuable data for testing the predictions of important frameworks such as the Metabolic Theory of Ecology ( MTE ) and ecological stoichiometry ( ES ). They also represent an important set of functional traits that may reflect both environmental and phylogenetic influences. Over the past two decades, studies of animal‐mediated nutrient cycling have increased dramatically, especially in aquatic ecosystems. Here we present a global compilation of aquatic animal nutrient excretion rates. The dataset includes 10,534 observations from freshwater and marine animals of N and/or P excretion rates. These observations represent 491 species, including most aquatic phyla. Coverage varies greatly among phyla and other taxonomic levels. The dataset includes information on animal body size, ambient temperature, taxonomic affiliations, and animal body N:P. This data set was used to test predictions of MTE and ES , as described in Vanni and McIntyre (2016; Ecology DOI : 10.1002/ecy.1582 ).

In Silico and In Vivo Experiments Reveal M-CSF Injections Accelerate Regeneration Following Muscle Laceration - Kyle S. Martin; Christopher D. Kegelman; Kelley M. Virgilio; Julianna A. Passipieri; George J. Christ; Silvia S. Blemker; Shayn M. Peirce (Annals of Biomedical Engineering, 2017)

Abrupt transition from fractional crystallization to magma mixing at Gorely volcano (Kamchatka) after caldera collapse - Maxim Gavrilenko; Alexey Ozerov; Philip R. Kyle; Michael J. Carr; Alex Nikulin; Christopher Vidito; Leonid Danyushevsky (Bulletin of Volcanology, 2016)

Phytoplankton growth and the interaction of light and temperature: A synthesis at the species and community level - Kyle F. Edwards; Mridul K. Thomas; Christopher A. Klausmeier; Elena Litchman (Limnology and Oceanography, 2016)
Temperature strongly affects phytoplankton growth rates, but its effect on communities and ecosystem processes is debated. Because phytoplankton are often limited by light, temperature should change community structure if it affects the traits that determine competition for light. Furthermore, the aggregate response of phytoplankton communities to temperature will depend on how changes in community structure scale up to bulk rates. Here, we synthesize experiments on 57 phytoplankton species to analyze how the growth‐irradiance relationship changes with temperature. We find that light‐limited growth, light‐saturated growth, and the optimal irradiance for growth are all highly sensitive to temperature. Within a species, these traits are co‐adapted to similar temperature optima, but light‐limitation reduces a species' temperature optimum by ∼5°C, which may be an adaptation to how light and temperature covary with depth or reflect underlying physiological correlations. Importantly, the maximum achievable growth rate increases with temperature under light saturation, but not under strong light limitation. This implies that light limitation diminishes the temperature sensitivity of bulk phytoplankton growth, even though community structure will be temperature‐sensitive. Using a database of primary production incubations, we show that this prediction is consistent with estimates of bulk phytoplankton growth across gradients of temperature and irradiance in the ocean. These results indicate that interactions between temperature and resource limitation will be fundamental for explaining how phytoplankton communities and biogeochemical processes vary across temperature gradients and respond to global change.

Seascape drivers of M acrocystis pyrifera population genetic structure in the northeast P acific - Mattias L. Johansson; Filipe Alberto; Daniel C. Reed; Peter T. Raimondi; Nelson C. Coelho; Mary A. Young; Patrick T. Drake; Christopher A. Edwards; Kyle Cavanaugh; Jorge Assis; Lydia B. Ladah; Tom W. Bell; et al. (Molecular Ecology, 2015)
At small spatial and temporal scales, genetic differentiation is largely controlled by constraints on gene flow, while genetic diversity across a species' distribution is shaped on longer temporal and spatial scales. We assess the hypothesis that oceanographic transport and other seascape features explain different scales of genetic structure of giant kelp, M acrocystis pyrifera . We followed a hierarchical approach to perform a microsatellite‐based analysis of genetic differentiation in M acrocystis across its distribution in the northeast P acific. We used seascape genetic approaches to identify large‐scale biogeographic population clusters and investigate whether they could be explained by oceanographic transport and other environmental drivers. We then modelled population genetic differentiation within clusters as a function of oceanographic transport and other environmental factors. Five geographic clusters were identified: A laska/ C anada, central C alifornia, continental S anta B arbara, C alifornia C hannel I slands and mainland southern C alifornia/ B aja C alifornia peninsula. The strongest break occurred between central and southern C alifornia, with mainland S anta B arbara sites forming a transition zone between the two. Breaks between clusters corresponded approximately to previously identified biogeographic breaks, but were not solely explained by oceanographic transport. An isolation‐by‐environment ( IBE ) pattern was observed where the northern and southern C hannel I slands clustered together, but not with closer mainland sites, despite the greater distance between them. The strongest environmental association with this IBE pattern was observed with light extinction coefficient, which extends suitable habitat to deeper areas. Within clusters, we found support for previous results showing that oceanographic connectivity plays an important role in the population genetic structure of M acrocystis in the Northern hemisphere.

Nutrient utilization traits of phytoplankton - Kyle F. Edwards; Christopher A. Klausmeier; Elena Litchman (Ecology, 2015)
This paper presents a compilation of nutrient utilization traits of marine and freshwater phytoplankton. The literature was comprehensively searched for culture experiments using nitrate, ammonium, or phosphate as the limiting nutrient. The following traits were extracted: the response of growth to nutrient supply (maximum growth rate under unlimited nutrient supply and the nutrient concentration at which growth is half‐saturated); the response of internal nutrient content to nutrient supply (the minimum subsistence quota at which growth ceases and the maximum nutrient quota under unlimited nutrient supply); and nutrient uptake kinetics for nutrient‐limited cells (maximum uptake rate and the nutrient concentration at which uptake is half‐saturated). The resulting data set includes 1319 measurements on 129 species from 138 publications. Potential uses of these data include studies of community structure and trait evolution, parameterization of ecosystem models, and biofuel development.

Fast maximum likelihood estimation using continuous-time neural point process models - Kyle Q. Lepage; Christopher J. MacDonald (Journal of Computational Neuroscience, 2015)

Isolation and characterization of novel Agrobacterium strains for soybean and sunflower transformation - Kyle A. Benzle; Kim R. Finer; DeeMarie Marty; Leah K. McHale; Brad W. Goodner; Christopher G. Taylor; John J. Finer (Plant Cell, Tissue and Organ Culture (PCTOC), 2015)

A Place Meaning Scale for Tropical Marine Settings - Christopher J. Wynveen; Gerard T. Kyle (Environmental Management, 2015)

The frequency of explosive volcanic eruptions in Southeast Asia - Patrick L. Whelley; Christopher G. Newhall; Kyle E. Bradley (Bulletin of Volcanology, 2015)

Development of nuclear microsatellite markers for American badger subspecies (Taxidea taxus spp.) using next generation sequencing - Yessica Rico; David Paetkau; Leanne R. Harris; Josh Sayers; Danielle Ethier; Christopher J. Kyle (Conservation Genetics Resources, 2014)

Spatial patterns of neutral and functional genetic variations reveal patterns of local adaptation in raccoon ( P rocyon lotor ) populations exposed to raccoon rabies - Christopher J. Kyle; Yessica Rico; Sarrah Castillo; Vythegi Srithayakumar; Catherine I. Cullingham; Bradley N. White; Bruce A. Pond (Molecular Ecology, 2014)
Local adaptation is necessary for population survival and depends on the interplay between responses to selective forces and demographic processes that introduce or retain adaptive and maladaptive attributes. Host–parasite systems are dynamic, varying in space and time, where both host and parasites must adapt to their ever‐changing environment in order to survive. We investigated patterns of local adaptation in raccoon populations with varying temporal exposure to the raccoon rabies virus ( RRV ). RRV infects approximately 85% of the population when epizootic and has been presumed to be completely lethal once contracted; however, disease challenge experiments and varying spatial patterns of RRV spread suggest some level of immunity may exist. We first assessed patterns of local adaptation in raccoon populations along the eastern seaboard of N orth A merica by contrasting spatial patterns of neutral (microsatellite loci) and functional, major histocompatibility complex ( MHC ) genetic diversity and structure. We explored variation of MHC allele frequencies in the light of temporal population exposure to RRV (0–60 years) and specific RRV strains in infected raccoons. Our results revealed high levels of MHC variation (66 DRB exon 2 alleles) and pronounced genetic structure relative to neutral microsatellite loci, indicative of local adaptation. We found a positive association linking MHC genetic diversity and temporal RRV exposure, but no association with susceptibility and resistance to RRV strains. These results have implications for landscape epidemiology studies seeking to predict the spread of RRV and present an example of how population demographics influence the degree to which populations adapt to local selective pressures.

Inhibition of Pseudogymnoascus destructans Growth from Conidia and Mycelial Extension by Bacterially Produced Volatile Organic Compounds - Christopher T. Cornelison; Kyle T. Gabriel; Courtney Barlament; Sidney A. Crow (Mycopathologia, 2014)

Incorporating Climate Science in Applications of the U.S. Endangered Species Act for Aquatic Species - MICHELLE M. MCCLURE; MICHAEL ALEXANDER; DIANE BORGGAARD; DAVID BOUGHTON; LISA CROZIER; ROGER GRIFFIS; JEFFREY C. JORGENSEN; STEVEN T. LINDLEY; JANET NYE; MELANIE J. ROWLAND; ERIN E. SENEY; AMY SNOVER; et al. (Conservation Biology, 2013)
Aquatic species are threatened by climate change but have received comparatively less attention than terrestrial species. We gleaned key strategies for scientists and managers seeking to address climate change in aquatic conservation planning from the literature and existing knowledge. We address 3 categories of conservation effort that rely on scientific analysis and have particular application under the U.S. Endangered Species Act (ESA): assessment of overall risk to a species; long‐term recovery planning; and evaluation of effects of specific actions or perturbations. Fewer data are available for aquatic species to support these analyses, and climate effects on aquatic systems are poorly characterized. Thus, we recommend scientists conducting analyses supporting ESA decisions develop a conceptual model that links climate, habitat, ecosystem, and species response to changing conditions and use this model to organize analyses and future research. We recommend that current climate conditions are not appropriate for projections used in ESA analyses and that long‐term projections of climate‐change effects provide temporal context as a species‐wide assessment provides spatial context. In these projections, climate change should not be discounted solely because the magnitude of projected change at a particular time is uncertain when directionality of climate change is clear. Identifying likely future habitat at the species scale will indicate key refuges and potential range shifts. However, the risks and benefits associated with errors in modeling future habitat are not equivalent. The ESA offers mechanisms for increasing the overall resilience and resistance of species to climate changes, including establishing recovery goals requiring increased genetic and phenotypic diversity, specifying critical habitat in areas not currently occupied but likely to become important, and using adaptive management. Incorporación de las Ciencias Climáticas en las Aplicaciones del Acta Estadunidense de Especies en Peligro para Especies Acuáticas

Functional traits explain phytoplankton responses to environmental gradients across lakes of the United States - Kyle F. Edwards; Elena Litchman; Christopher A. Klausmeier (Ecology, 2013)
Ecological communities exhibit regular shifts in structure along environmental gradients, but it has proved difficult to dissect the mechanisms by which environmental conditions determine the relative success of species. Functional traits may provide a link between environmental drivers and mechanisms of community membership, but this has not been well tested for phytoplankton, which dominate primary production in many aquatic ecosystems. Here we test whether functional traits of phytoplankton can explain how species respond to gradients of light and phosphorus across U.S. lakes. We find that traits related to light utilization and maximum growth rate can predict species' differential responses to the relative availability of these resources. These results show that laboratory‐measured traits are predictive of species' performance under natural conditions, that functional traits provide a mechanistic foundation for community ecology, and that variation in community structure is predictable in spite of the complexity of ecological communities.

Functional traits explain phytoplankton community structure and seasonal dynamics in a marine ecosystem - Kyle F. Edwards; Elena Litchman; Christopher A. Klausmeier (Ecology Letters, 2013)
A fundamental yet elusive goal of ecology is to predict the structure of communities from the environmental conditions they experience. Trait‐based approaches to terrestrial plant communities have shown that functional traits can help reveal the mechanisms underlying community assembly, but such approaches have not been tested on the microbes that dominate ecosystem processes in the ocean. Here, we test whether functional traits can explain community responses to seasonal environmental fluctuation, using a time series of the phytoplankton of the English Channel. We show that interspecific variation in response to major limiting resources, light and nitrate, can be well‐predicted by lab‐measured traits characterising light utilisation, nitrate utilisation and maximum growth rate. As these relationships were predicted a priori , using independently measured traits, our results show that functional traits provide a strong mechanistic foundation for understanding the structure and dynamics of ecological communities.

Genetic isolation of wolverine (Gulo gulo) populations at the eastern periphery of their North American distribution - Joanna Zigouris; F. Neil Dawson; Jeff Bowman; Roxanne M. Gillett; James A. Schaefer; Christopher J. Kyle (Conservation Genetics, 2012)

Evidence for evolutionary convergence at MHC in two broadly distributed mesocarnivores - Vythegi Srithayakumar; Sarrah Castillo; Julien Mainguy; Christopher J. Kyle (Immunogenetics, 2012)

Allometric scaling and taxonomic variation in nutrient utilization traits and maximum growth rate of phytoplankton - Kyle F. Edwards; Mridul K. Thomas; Christopher A. Klausmeier; Elena Litchman (Limnology and Oceanography, 2012)
Nutrient utilization traits can be used to link the ecophysiology of phytoplankton to population dynamic models and the structure of communities across environmental gradients. Here we analyze a comprehensive literature compilation of four traits: maximum nutrient uptake rate; the half‐saturation constant for nutrient uptake; the minimum subsistence quota, measured for nitrate and phosphate; and maximum growth rate. We also use these traits to analyze two composite traits, uptake affinity and scaled uptake affinity. All traits tend to increase with cell volume, except for scaled uptake affinity and maximum growth rate, which tend to decline with cell volume. Most scaling relationships are the same for freshwater and marine species, although important differences exist. Most traits differ on average between major taxa, but between‐taxon variation is nearly always due to between‐taxon variation in volume. There is some evidence for between‐trait correlations that could constrain trait evolution, but these correlations are difficult to disentangle from correlation driven by cell volume. These results should enhance the parameterization of models that use size or taxonomic group to structure physiological variation in phytoplankton communities.

Predicting Species Distributions from Samples Collected along Roadsides - KYLE P. MCCARTHY; ROBERT J. FLETCHER JR; CHRISTOPHER T. ROTA; RICHARD L. HUTTO (Conservation Biology, 2012)
Predictive models of species distributions are typically developed with data collected along roads. Roadside sampling may provide a biased (nonrandom) sample; however, it is currently unknown whether roadside sampling limits the accuracy of predictions generated by species distribution models. We tested whether roadside sampling affects the accuracy of predictions generated by species distribution models by using a prospective sampling strategy designed specifically to address this issue. We built models from roadside data and validated model predictions at paired locations on unpaved roads and 200 m away from roads (off road), spatially and temporally independent from the data used for model building. We predicted species distributions of 15 bird species on the basis of point‐count data from a landbird monitoring program in Montana and Idaho (U.S.A.). We used hierarchical occupancy models to account for imperfect detection. We expected predictions of species distributions derived from roadside‐sampling data would be less accurate when validated with data from off‐road sampling than when it was validated with data from roadside sampling and that model accuracy would be differentially affected by whether species were generalists, associated with edges, or associated with interior forest. Model performance measures (kappa, area under the curve of a receiver operating characteristic plot, and true skill statistic) did not differ between model predictions of roadside and off‐road distributions of species. Furthermore, performance measures did not differ among edge, generalist, and interior species, despite a difference in vegetation structure along roadsides and off road and that 2 of the 15 species were more likely to occur along roadsides. If the range of environmental gradients is surveyed in roadside‐sampling efforts, our results suggest that surveys along unpaved roads can be a valuable, unbiased source of information for species distribution models.

Phylogenetic density dependence and environmental filtering predict seedling mortality in a tropical forest - C. E. Timothy Paine; Natalia Norden; Jérôme Chave; Pierre‐Michel Forget; Claire Fortunel; Kyle G. Dexter; Christopher Baraloto (Ecology Letters, 2012)
Ecology Letters (2011) 14 : 34–41 Abstract Negative density dependence (NDD) and environmental filtering (EF) shape community assembly, but their relative importance is poorly understood. Recent studies have shown that seedling’s mortality risk is positively related to the phylogenetic relatedness of neighbours. However, natural enemies, whose depredations often cause NDD, respond to functional traits of hosts rather than phylogenetic relatedness per se . To understand the roles of NDD and EF in community assembly, we assessed the effects on seedling mortality of functional similarity, phylogenetic relatedness and stem density of neighbouring seedlings and adults in a species‐rich tropical forest. Mortality risks increased for common species when their functional traits departed substantially from the neighbourhood mean, and for all species when surrounded by close relatives. This indicates that NDD affects community assembly more broadly than does EF, and leads to the tentative conclusion that natural enemies respond to phylogenetically correlated traits. Our results affirm the prominence of NDD in structuring species‐rich communities.

The Business of Forest Enterprise / Urban Ecosystems / Forest Policy / Biosecurity - David Nicholls; Allen Brackley; Charles Keegan; Colin Sorenson; Jean Daniels; Erik Berg; Charles Gale; Robert Campbell; Charles Gale; Charles Keegan; Erik Berg; Colin Sorenson; et al. (Journal of Forestry, 2011)
172Business clusters are geographic concentrations of companies that provide mutual advantages for their participants. Clusters can include diverse members including competitors, customers, partners, and/or suppliers. In Alaska, wood products business clusters can have unique challenges associated with remote locations, high raw material costs, limited local markets, and potentially long transportation distances. Further, multiple land ownership near communities (for example state versus federal ownership) can influence raw material procurement, since different administrative processes for timber harvesting may be required. This study evaluates 2 resource dependent communities in southeast Alaska (Haines, AK and Craig, AK), seeking to identify elements that could enhance their potential for wood products clusters and new business formation. We consider how the flow of forest resources, from harvest to finished product, can influence local communities and either enhance or limit opportunities for wood products businesses. We evaluate the effect of various product mixes—including firewood, woody residues, house logs, lumber, and secondary wood products—on the composition, scale, and dynamics of wood products firms. We consider the effect of harvesting practices and proximity to timber sales in evaluating how land ownership can influence the viability of wood products clusters. Lastly we consider the impact of transportation costs on serving local and export markets. Our research builds upon past work in Alaska that evaluated national-forest based communities in Alaska, finding opportunities for greater innovation, higher productivity, and greater social well-being associated with wood products clusters.

Pacific Rim Forestry / Silviculture and Forest Ecology - Vishal Singh Negi; Archana Pal; Ratnesh Singh; Dulal Borthakur; Archana Pala; Vishal Singh Negi; Dulal Borthakur; Isabel Rushanaedy; Tyler Jones; Nicklos Dudley; Dulal Borthakur; Jannai Yafuso; et al. (Journal of Forestry, 2011)
Leucaena leucocephala (leucaena) is an important agroforestry tree of tropics and subtropics due to its protein rich foliages, ability to grow on poor soils, and high level of tolerance to various stresses including drought and diseases. We hypothesized that leucaena have a unique set of genes which confer tolerance to various abiotic and biotic stresses and these genes are either absent or not expressed in other legumes that are susceptible to these stress conditions. Interspecies suppression subtractive hybridization (iSSH) was performed to identify some unique genes from leucaena using cDNAs from leucaena and Acacia confusa (acacia) as the tester and driver, respectively. We identified 100 leucaena genes showing homology to various plant genes with known functions, of which 23 genes had homology to various stress-related proteins including chitinase, PR-10 protein, wound-stress protein, type-2 metallothionein, thaumatin-like protein, disease resistance response protein, cysteine proteinase, and kunitz trypsin inhibitor. We also identified 50 leucaena genes which either had homology to hypothetical proteins (HyPs) or had no homology at all. Putative functions of 15 HyPs were predicted using conserved domain and PSI-BLAST analyses. Linear motif analyses identified 17 HyPs with MAPK recognition motif, which is involved in signaling pathways, including stress responses. This study identified 23 known and some putative unique stress-related genes from leucaena which may serve as a useful source of stress-tolerance genes for tree and crop improvement in the future.

MHC class II DRB diversity in raccoons (Procyon lotor) reveals associations with raccoon rabies virus (Lyssavirus) - Vythegi Srithayakumar; Sarrah Castillo; Rick C. Rosatte; Christopher J. Kyle (Immunogenetics, 2011)

Differential permeability of rivers to raccoon gene flow corresponds to rabies incidence in Ontario, Canada - CATHERINE I. CULLINGHAM; CHRISTOPHER J. KYLE; BRUCE A. POND; ERIN E. REES; BRADLEY N. WHITE (Molecular Ecology, 2009)
The correlation of landscape features with genetic discontinuities reveals barriers to dispersal that can contribute to understanding present and future spread of wildlife diseases. This knowledge can then be used for targeting control efforts. The impact of natural barriers on raccoon dispersal was assessed through genetic analysis of samples from two regions, Niagara ( N = 666) and St. Lawrence ( N = 802). These areas are transected by major rivers and are at the northern front of a raccoon rabies epizootic. Genetic clusters were identified in each region using Bayesian clustering algorithms. In the Niagara region, two clusters were identified corresponding to either side of the Niagara River. For the St. Lawrence region, spatially congruent clusters were not identified, despite the presence of the intervening St. Lawrence River. These genetic data are consistent with raccoon rabies incidence data where rabies has been detected across the St. Lawrence River in Ontario while no cases have been detected in Ontario across the Niagara River. This is despite expectations of rabies incidence in Niagara before the St. Lawrence based on the progression of rabies from New York. The results from the two regions suggest different permeabilities to raccoons between New York and Ontario that may be attributed to the rivers. However, other factors have also been explored that could contribute to this difference between these study sites including the shape of the landscape and resource distribution.

Testing metabolic ecology theory for allometric scaling of tree size, growth and mortality in tropical forests - Helene C. Muller‐Landau; Richard S. Condit; Jerome Chave; Sean C. Thomas; Stephanie A. Bohlman; Sarayudh Bunyavejchewin; Stuart Davies; Robin Foster; Savitri Gunatilleke; Nimal Gunatilleke; Kyle E. Harms; Terese Hart; et al. (Ecology Letters, 2006)
The theory of metabolic ecology predicts specific relationships among tree stem diameter, biomass, height, growth and mortality. As demographic rates are important to estimates of carbon fluxes in forests, this theory might offer important insights into the global carbon budget, and deserves careful assessment. We assembled data from 10 old‐growth tropical forests encompassing censuses of 367 ha and > 1.7 million trees to test the theory's predictions. We also developed a set of alternative predictions that retained some assumptions of metabolic ecology while also considering how availability of a key limiting resource, light, changes with tree size. Our results show that there are no universal scaling relationships of growth or mortality with size among trees in tropical forests. Observed patterns were consistent with our alternative model in the one site where we had the data necessary to evaluate it, and were inconsistent with the predictions of metabolic ecology in all forests.

Comparing tropical forest tree size distributions with the predictions of metabolic ecology and equilibrium models - Helene C. Muller‐Landau; Richard S. Condit; Kyle E. Harms; Christian O. Marks; Sean C. Thomas; Sarayudh Bunyavejchewin; George Chuyong; Leonardo Co; Stuart Davies; Robin Foster; Savitri Gunatilleke; Nimal Gunatilleke; et al. (Ecology Letters, 2006)
Tropical forests vary substantially in the densities of trees of different sizes and thus in above‐ground biomass and carbon stores. However, these tree size distributions show fundamental similarities suggestive of underlying general principles. The theory of metabolic ecology predicts that tree abundances will scale as the −2 power of diameter. Demographic equilibrium theory explains tree abundances in terms of the scaling of growth and mortality. We use demographic equilibrium theory to derive analytic predictions for tree size distributions corresponding to different growth and mortality functions. We test both sets of predictions using data from 14 large‐scale tropical forest plots encompassing censuses of 473 ha and > 2 million trees. The data are uniformly inconsistent with the predictions of metabolic ecology. In most forests, size distributions are much closer to the predictions of demographic equilibrium, and thus, intersite variation in size distributions is explained partly by intersite variation in growth and mortality.

40Ar/39Ar dating of the eruptive history of Mount Erebus, Antarctica: summit flows, tephra, and caldera collapse - Christopher J. Harpel; Philip R. Kyle; Richard P. Esser; William C. McIntosh; David A. Caldwell (Bulletin of Volcanology, 2004)